2022
DOI: 10.24912/jmk.v4i1.17118
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Variabel Makroekonomi dan Rasio Keuangan terhadap Harga Saham

Abstract: Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh dari tingkat inflasi, tingkat suku bunga, nilai tukar/kurs dan Return on Asset (ROA) terhadap harga saham perusahaan yang tergabung ke dalam Indeks LQ45 Bursa Efek Indonesia periode 2016-2020. Sampel penelitian ini adalah sebanyak 27 sampel yang dipilih berdasarkan metode purposive sampling. Data pada penelitian ini menggunakan data sekunder yang diperoleh dari situs Bursa Efek Indonesia, situs Bank Indonesia, situs Badan Pusat Statistik dan si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In such a scenario, people's demand for holding cash decreases because they are more inclined to allocate their funds to various banking options such as deposits and savings. Recent studies conducted by (Bagaswara & Wati, 2020) (Novriyani, 2021) (Nurulhuda & Kosasih, 2019) (Rasudu, 2021) (Wijaya & MN, 2022) have found that interest rates have a significant impact on firm value. Therefore, it can be concluded that interest rates play an important role in investment decisions and can affect the value of firms: H1: Interest rates affect Firm Value.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…In such a scenario, people's demand for holding cash decreases because they are more inclined to allocate their funds to various banking options such as deposits and savings. Recent studies conducted by (Bagaswara & Wati, 2020) (Novriyani, 2021) (Nurulhuda & Kosasih, 2019) (Rasudu, 2021) (Wijaya & MN, 2022) have found that interest rates have a significant impact on firm value. Therefore, it can be concluded that interest rates play an important role in investment decisions and can affect the value of firms: H1: Interest rates affect Firm Value.…”
Section: Theoretical Reviewmentioning
confidence: 99%